PENGARUH MODEL PEMBELAJARAN DAN KEMAMPUAN METAKOGNTIF TERHADAP PEMAHAMAN KONSEP FISIKA - Emanuel Gentur; I Made Astra; Erfan Handoko (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2014)
This research aims to know 1) the difference between the concept of optical tools toward learning model, 2) the difference of metacognitive ability toward the concept of optical tools and, 3) the impact of the interaction between learning model and metacognitive ability. The subject target of this research are the student of grade 10 students majoring at natural scince ( X-MIA) of Penabur Christian Senior High School 3 Jakarta ( SMAK 3 Penabur Jakarta ) academic year 2013/2014. The research model user experimental quatient method which are devided into two group without controlling group. The design of this research user treatment by level 2x2 using variety analysis technique ( ANAVA) two directions with interaction. The data of metacognitive ability is gathered using statement questionare totalling 50 statements using Linkert scale model. The validation test of metacognitive instrument uses the correlation of product moment and the test of reliability uses Alpha Cronbach technique. After being validated the instrument used are only 35 questionare. The data of comprehension of the optical tools concept uses multiple choice test consisting 25 questions which are validated using Biserial correlation point and reliability test uses Kuder and Richardson technique ( KR-21). The data are analized using pre-conditional test which uses normality test of Liliefors and homogenity test using Fisher test( test F) and Barlett test. The result of this researh shows : 1) ther is no difference of the comprehension of the concept of optical tools against learning model, 2) there is no influence of learning model interaction and metacognitive ability, 3) there is a difference of comprehension of the concept of optical tools against metacognitive ability. Key words : problem posing, problem solving, metacognitve.